Analysis of typical Lithuanian features in the context of accession to the European union - Šimanskiene, Ligita (Journal of Business Economics and Management, 2004)
The work reviews the influence of cross‐cultural features in management in the context of globalization. The work analyses the particular characteristics of a national stereotype of a Lithuanian based on the survey of other authors. Several hypotheses have been suggested based on SPSS programmer during the survey. The research has corroborated that the correct reasoning of typical characteristic features of a Lithuanian depends on age, position, sex, while the hypothesis 4, asserting that the correct reasoning of typical characteristic features of a Lithuanian depends on education, hasn't been corroborated according to statistics and the variety of answers was due to different personal characteristics of respondents. Also the work analyses future forecasts for Lithuania in the European Union.First Published Online: 14 Oct 2010